Patterns of antibody responses to nonviral cancer antigens in head and neck squamous cell carcinoma patients differ by human papillomavirus status. Issue 12 (26th August 2019) - Gangkofner, Dominik S.; Holzinger, Dana; Schroeder, Lea; Eichmüller, Stefan B.; Zörnig, Inka; Jäger, Dirk; Wichmann, Gunnar; Dietz, Andreas; Broglie, Martina A.; Herold‐Mende, Christel; Dyckhoff, Gerhard; Boscolo‐Rizzo, Paolo; et al.
Abstract : There have been hints that nonviral cancer antigens are differentially expressed in human papillomavirus (HPV)‐positive and HPV‐negative head and neck squamous cell carcinoma (HNSCC). Antibody responses (AR) to cancer antigens may be used to indirectly determine cancer antigen expression in the tumor using a noninvasive and tissue‐saving liquid biopsy. Here, we set out to characterize AR to a panel of nonviral cancer antigens in HPV‐positive and HPV‐negative HNSCC patients. A fluorescent microbead multiplex serology to 29 cancer antigens (16 cancer‐testis antigens, 5 cancer‐retina antigens and 8 oncogenes) and 29 HPV‐antigens was performed in 382 HNSCC patients from five independent cohorts (153 HPV‐positive and 209 HPV‐negative). AR to any of the cancer antigens were found in 272/382 patients (72%). The ten most frequent AR were CT47, cTAGE5a, c‐myc, LAGE‐1, MAGE‐A1, ‐A3, ‐A4, NY‐ESO‐1, SpanX‐a1 and p53. AR to MAGE‐A3, MAGE‐A9 and p53 were found at significantly different prevalences by HPV status. An analysis of AR mean fluorescent intensity values uncovered remarkably different AR clusters by HPV status. To identify optimal antigen selections covering a maximum of patients with ≤10 AR, multiobjective optimization revealed distinct antigen selections by HPV status. We identified that AR to nonviral antigens differ by HPV status indicating differential antigen expression. Multiplex serology may be used to characterize antigen expression using serum or plasma as a tissue‐sparing liquid biopsy. Cancer antigen panels should address the distinct antigen repertoire of HPV‐positive and HPV‐negative HNSCC. Abstract : What's new? Head and neck squamous cell carcinoma remains a deadly disease but new immunotherapeutic approaches are underexplored. Here the authors tested for antibody responses against human antigens to characterize the expression of such antigens in tumors positive or negative for human papillomavirus (HPV). Antibody responses were significantly different in prevalence and pattern based on HPV‐status in a large patient cohort. The authors urge independent confirmation of their results but point out that multiplex serology of tumor antigens could be a promising strategy to identify immunotherapeutic targets based on HPV status.